An analysis of the factors affecting university students intention to use mobile commerce: an extended TPB - Haque, A. K. M. Ahasanul (Human Resource Management Academic Research Society (HRMARS), 2024)
Mobile commerce has recently surged in popularity because of mobile and communications technology developments. This study investigates the factors affecting Malaysian university students' behavioural intention to use mobile commerce. The theory of planned behaviour is utilised. Surveys were distributed to university students in Malaysia via an online Google Form, generating 250 usable responses. A two-stage structural equation modelling was used to test the study's hypotheses. The results indicate that attitude, subjective norm, and perceived behavioural control significantly affect the behavioural intention to use mobile commerce. In contrast, perceived security does not significantly affect the intention to use mobile commerce. Hence, these findings will benefit mobile commerce providers, merchants, students, consumers, academicians, and other industry players. The study enhances comprehension of the factors influencing the behavioural intention of Malaysian university students to use mobile commerce. This study extended the theory of planned behaviour in mobile commerce use by including perceived security. The extended theory of planned behaviour enhances the understanding of Malaysian university students' intention to engage in mobile commerce. However, the study discusses the implications of these findings for managers. It proposes alternatives for future researchers who wish to examine factors affecting university students’ behavioural intention to use mobile commerce in Malaysia or any other country.